Geriatric depression in advanced cancer patients: The effect of cognitive and physical functioning. Issue 2 (14th June 2012) - Mystakidou, Kyriaki; Parpa, Efi; Tsilika, Eleni; Panagiotou, Irene; Zygogianni, Anna; Giannikaki, Eugenia; Gouliamos, Athanasios
<x xml:space="preserve">Abstract</x> Aim: The aims of the current study were to evaluate geriatric depression and its risk factors in advanced cancer patients. Methods: A cross‐sectional study was carried out in a palliative care unit in Greece. Patients completed the Geriatric Depression Scale, the M. D. Anderson Symptoms Instrument (MDASI), the Activities of Daily Living and the Mini‐Mental State Examination. Patients were included if they were aged >65 years, if they had cancer, were able to communicate and had agreed to sign informed consent. The final sample consisted of 92 elderly advanced cancer patients. Results: The prevalence of depression was found to be 67.4%. The univariate comparison between the depressed elderly and non‐depressed group showed that patients with metastases were found to be 2.2‐fold more likely to suffer from geriatric depression compared with those without metastases (P = 0.074). Patients with moderate or severe cognitive impairment were found to be 3.61‐fold more likely to suffer from geriatric depression in comparison with those with normal cognitive function (P = 0.019). In the multiple logistic regression analysis, elderly with cognitive impairment were 3.3‐fold more likely to have geriatric depression than those without (adjusted odds ratio = 3.3 [95% CI 0.99–10.74], P = 0.052) and MDASI factor 1 was consistently a significant risk factor for depression in the elderly; when MDASI factor 1 increased by 1 unit, the odds of being classified as depressed increased by 7.6%. Conclusions: The present study found that cognitive impairment and symptoms such as enjoyment of life, walking, relationship with people, general activity, sadness and pain (MDASI F1) are strong independent predictors of depression in the elderly. Geriatr Gerontol Int 2013; 13: 281–288..